2006
DOI: 10.1007/s10722-005-2434-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Soybean (Glycine Max (L.) Merrill)7S Globulin Protein Subunits

Abstract: Out of 851 soybean accessions from Vietnam, China and Japan analyzed for 7S b-subunit variants, a new b-reduced subunit line with normal growth was collected from the Mekong Delta, Vietnam. Protein of the 'b-reduced' line is composed of b-reduced and extremely low-b types. (a-null + b-reduced) type and b-null (or extremely low-b) type were screened in the progeny seeds of the Japanese mutant '(a + b) null' line. Therefore, recombination between a-and b-subunits was identified. By comparing the nucleotide seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Variation in storage proteins among genotypes has been reported previously in peas as well as soybeans. , Zilic et al analyzed β-conglycinin and glycinin subunits in seven soybean genotypes by SDS-PAGE and reported that the amounts of the various subunits varied among genotypes. Liu et alalso used SDS-PAGE to analyze β-conglycinin in 851 soybean accessions from Vietnam, China, and Japan and reported genetic variability among them.…”
Section: Resultsmentioning
confidence: 99%
“…Variation in storage proteins among genotypes has been reported previously in peas as well as soybeans. , Zilic et al analyzed β-conglycinin and glycinin subunits in seven soybean genotypes by SDS-PAGE and reported that the amounts of the various subunits varied among genotypes. Liu et alalso used SDS-PAGE to analyze β-conglycinin in 851 soybean accessions from Vietnam, China, and Japan and reported genetic variability among them.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the β subunit of β-conglycinin is not a desirable soybean protein subunit because it contains no methionine residues . Therefore, by producing a recombinant β-conglycinin subunit with suppressed expression of the β subunit of soybean β-conglycinin, it should be possible to improve the quality of soybean . In previous studies, several mutants of 7S globulin subunits were obtained. ,,, Manjaya et al reported that the mutants M-17 and M-231 can be identified by the lack of α′ and α subunits of β-conglycinin and by increased levels of β subunits of β-conglycinin.…”
Section: Discussionmentioning
confidence: 99%
“…Diversity in SSP composition has been reported in various crop species such as wheat [ 245 ] and soybean [ 246 ], implying similar diversity may exist in canola. Wild soybean accessions with unique SSP profiles have been successfully incorporated into breeding programs to generate segregating populations with variable seed protein profiles [ 247 ] indicating that the manipulation of storage protein composition can be achieved by conventional breeding.…”
Section: Manipulation Of Seed Storage Proteins In Select Crop Speciesmentioning
confidence: 99%